Evaluation of the shaping ability of two reciprocating systems: Reciproc Blue x V-File (Research, Society and Development, 2021)
Introduction: Cleaning and shaping are extremely important steps in the instrumentation of root canals so that endodontic treatment can be carried out with excellence. With the aim of optimizing working time and presenting a high-quality material, NiTi (nickel-titanium) files have been developed to ensure successful endodontic treatment. Acrylic blocks are used to obtain a pattern of simulated canals. Objective: The aim of this study was to compare Reciproc Blue and V-File files after their second use. Methods: 40 acrylic blocks were used, divided into four groups (n=10) according to the number of times each instrument was used: REC1, REC2, VF1 and VF2. Prior to root canal preparation, the patency of the root canal was checked with a #10 K file. Pre- and postoperative photographic images were created in image processing software (Adobe Photoshop CS5.1) for later superimposition and analysis. Statistical analysis was performed using the t-test and Mann Whitney test. Results: At all points studied, the Reciproc Blue instrument removed more resin from the outside at the beginning of the curve (p < 0.05). There were no significant differences at any of the points in terms of transport distance from the canal. The Reciproc Blue instrument had wider and less conservative preparations. Conclusion: Both instruments (Reciproc Blue and V-File) are safe for curved canal preparation and provide effective cleaning and shaping. However, the V-File instrument had more conservative preparations.